En-Bloc Kidney Transplantation From Extremely Low-Weight (0.9–5.0 kg) Pediatric Donors: A Decade of Single-Center Experience - Xianpeng Zeng; Qiuxiang Xia; Heng Li; Miao Wang; Hanying Li; Liang He; Hua Su; Chun Zhang; Zhendi Wang (Transplant International)
En-bloc kidney transplantation from low-weight pediatric donors (≤5 kg) is a challenging procedure performed only in limited transplant centers. We retrospectively analyzed the data from 42 en-bloc kidney transplants from donors weighing less than 5 kg between September 2014 and September 2023. The mean donor body weight was found to be 3.1 ± 1.0 kg, and the minimum weight was 0.9 kg. At a mean follow-up period of 1,481 days, the graft survival rate was 76.2% and the recipient survival rate was 100.0%. Thrombosis and acute rejection were the major complications responsible for the short-term graft loss. Male recipients were more likely to experience graft loss than female ones (P < 0.05). Recipients with long-term (>1 year) graft survival were observed to have a high prevalence (31.3%) of delayed graft function. However, they still had satisfactory long-term graft function and limited proteinuria. Continuous graft volume growth took more than 1 year to reach a stable level. Lower donor/recipient body surface area may lead to higher delayed graft function and slower estimated glomerular filtration rate recovery (P < 0.05). Kidney transplant from low-weight pediatric donors is associated with a high incidence of short-term graft loss, while long-term outcomes are generally acceptable.